Strategi Guru Bidang Studi PKn dalam Penanaman Nilai-Nilai Demokrasi Pancasila di SMK PGRI 3 Salatiga - undaris, Praptiningsih (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2022)
This article discusses about the strategy of civic education teacher in instilling democratic values of Pancasila at SMK PGRI 3 Salatiga. This study used a qualitative approach. The informants in this study were 1 teacher and 20 students of class XI. The data collection techniques carried out in this study used observation, interviews, and documentation. Data analysis includes three steps : data categorization, data description, and conclusions. The results showed that the strategy of civic education teacher in instilling democratic values of Pancasila at SMK PGRI 3 Salatiga was by using learning models or methods including discovery learning, problem based learning, and project based learning. However of the three models or methods, teacher tend to use discovery learning and use approaches related to the democratic values of Pancasila in every learning process, both in the classroom and outside the classroom.Keywords: teacher strategy, democratic values of Pancasila